Cerebral Stroke After Valvular Surgery in Young Patients: Case Studies - Ravi Ghatanatti; Sundeep Sanjivan Tirkey; Anita Teli (Journal of Clinical and Diagnostic Research, 2014)
Intracranial haemorrhage (ICH) is a dreaded complication caused by oral anticoagulants (OAC) after valvular heart surgeries. Anticoagulant use in conventional doses increases the risk of ICH 7-10 fold. Intracerebral haematomas constitute 70% of the anticoagulant-related intracranial haemorrhages, with mortalities approaching 60%. Predisposing factors for anticoagulant-related ICH in Indian patients are unique as compared to those seen in their western counterparts. In anticoagulated patients, ICH evolves rapidly within hours; hence, emergency reversal of anticoagulation is crucial. We are reporting four cases of cerebral strokes which followed valvular surgeries in our institution, who were admitted during August 2012 to July 2013. There is an increasing need to educate the patients and update the physicians regarding the various issues which are involved in anticoagulation management.